AVALIAÇÃO DOS TEMPOS DESTINADOS A ATIVIDADES DE TRANSPORTE NUMA OBRA DE PAREDE DE CONCRETO MOLDADO IN LOCO - Teixeira, Matheus Ivanoski; Alberte, Elaine Pinto Varela; Perez, Cristina Toca (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This paper presents the results of an empirical study carried out in a residential building project in the Northeast of Brazil, which involved the use of the reinforced concrete walls structure as main construction technology. The main goal of this study was measuring the time waste in transportation activities in the construction technology used. To achieve that goal 16 field visits were performed and some source of evidences were used, such as photos, document analyses and informal interviews with labor force. The main contributions of this study are concerned with the integrated used of the Process Flow Diagram and Layout Diagram tools and the technique Work Sampling for the understanding the main time-consuming activities in construction projects. Moreover, the necessity of planning flow activities is point out as a fundamental task in industrialized processes.